Remuneração variável nas empresas brasileiras : estudo de determinantes da utilização de Stock Options - Warley de Oliveira Dias (2010)
Stock options plans are repeatedly used by companies around the world for more than 50 years. Such incentive is spreading in the Brazilian market in recent years. These plans fundamentations come from the Agency Theory, as form to minimize the conflicts between principal and agent. Thus, this study purpose was to identify factors that explain the usage of stock options plans as remuneration for Brazilian companies, according to the Agency Theory. Specifically, we sought to identify the main characteristics of stock options plans, the existence of differences in the companies characteristics, using distinct plans for stockoptions, and differences in the characteristics among companies that grant stock options as remuneration and those that do not grant. To this end, we carried out a descriptiveexplanatory search, using the 2009 financial statements from Brazilian companies. The sample consisted of 237 (two hundred and thirty-seven) companies, from which 85 (eightyfive)had plans to stock options. Seven hypotheses were established, being the Economatica system the main database, using the logit regression technique for data analysis. As a result, we found Capital Concentration, Dimension, Growth Opportunity, Foreign Ownership, and Regulation as the variables that explain the usage of stock options in these companies group. We conclude that the used variables in international studies to explain the usage of stock options also applies to Brazilian market, especially if they are used together as in this research. However, the results are not conclusive from the various researches about thesubject.